2018
DOI: 10.1111/evo.13637
|View full text |Cite
|
Sign up to set email alerts
|

Evolvability and craniofacial diversification in genus Homo

Abstract: There is abundant theoretical and empirical evidence for the influence of variational properties of populations on microevolution, and more limited support for their lasting impact during macroevolution. This study applies evolutionary quantitative genetic approaches to assess the long-term impact of within-population phenotypic variation and covariation (the P matrix) on population divergence in recent humans and species diversification in genus Homo. Similarity between the primary axes of within-and between-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 72 publications
1
13
0
Order By: Relevance
“…Therefore, the recent H. sapiens pooled within-population P matrices for the occipital and frontal bones were used as proxies for H. erectus. H. sapiens was chosen because it is the closest extant phylogenetic match for H. erectus [49,52,80] and the human P matrix is a good estimate of its G matrix [81][82][83]. In total, 145 recent H. sapiens from three populations with n ∼ 50 each were used to calculate the pooled within-population covariance matrices that were used as proxies for H. erectus in testing Prediction 3 (electronic supplementary material, table S3).…”
Section: (B) Predictionmentioning
confidence: 99%
“…Therefore, the recent H. sapiens pooled within-population P matrices for the occipital and frontal bones were used as proxies for H. erectus. H. sapiens was chosen because it is the closest extant phylogenetic match for H. erectus [49,52,80] and the human P matrix is a good estimate of its G matrix [81][82][83]. In total, 145 recent H. sapiens from three populations with n ∼ 50 each were used to calculate the pooled within-population covariance matrices that were used as proxies for H. erectus in testing Prediction 3 (electronic supplementary material, table S3).…”
Section: (B) Predictionmentioning
confidence: 99%
“…Not surprisingly, these models have inspired a large literature (e.g., Baab, 2018; Goswami et al, 2014; Grabowski et al, 2011; Haber, 2016; Marroig et al, 2009; Shirai & Marroig, 2010). Most estimate phenotypic rather than genetic covariance matrices and compare these among taxa before reconstructing selection gradients and analyzing the directions and rates of evolutionary change One recent study estimated G for seven species of West Indian Anolis lizards and found that evolutionary change is strongly biased in the direction of the major axis of G for over 40 million years even though G itself evolved (McGlothlin et al, 2018).…”
Section: What Does Modularity Mean For Evolution?mentioning
confidence: 99%
“…In addition, the richness of the fossil record varies substantially among taxa, and not all fossil species have sufficient sample sizes to robustly estimate P. Cheverud (1988) suggested at least 40 individuals were needed for a reasonably accurate P for G substitution, but larger sample sizes are required as the number of traits increase and to accurately estimate some evolvability statistics (Grabowski and Porto 2017). One potential solution is to use P (or G) matrices from extant species as a substitute for unknown fossil G matrices (Ackermann and Cheverud 2004;Young et al 2010;Grabowski et al 2011;Hansen and Voje 2011;Grabowski and Roseman 2015;Baab 2018). This assumes that the estimated P or G from the extant population is similar enough to G in the ancestral, extinct population.…”
Section: Quantitative Genetics In the Rock Recordmentioning
confidence: 99%